Guidance for the identification of bony lesions related to smallpox - Crawford, Rosie R.; Hodson, Claire M.; Errickson, David (Elsevier, 2024)
Objective: This research aimed to address the underrepresentation of smallpox (osteomyelitis variolosa) in palaeopathology, providing a synthesis of published literature and presenting guidance for the identification of osteomyelitis variolosa in non-adult and adult skeletal remains. Materials and methods: Literature regarding smallpox and published reports of individuals with osteomyelitis variolosa were synthesised and critiqued to produce clear diagnostic criteria for the identification of smallpox osteologically. Results: Associated osteological changes begin in non-adults, where skeletal morphology is rapidly changing. Characteristic lesions associated with non-adult osteomyelitis variolosa include inflammation and destructive remodelling of long-bone joints and metaphyses. Where childhood infection was survived, residual osteomyelitis variolosa lesions should also be visible in adults in the osteoarchaeological record. Conclusions: Despite long-term clinical recognition, only limited osteological and archaeological evidence of osteomyelitis variolosa has yet emerged. With improved diagnostic criteria, osteomyelitis variolosa may be more frequently identified. Significance: This is the first synthesis of osteomyelitis variolosa encompassing both clinical and palaeopathological literature, providing detailed guidance for the identification of osteomyelitis variolosa in skeletal remains. It will lead to the increased identification of smallpox osteologically. Limitations: Differential diagnoses should always be considered. The archaeological longevity of smallpox, and the potential for archaeological VARV to cause clinically recognised smallpox, is currently unknown. Characteristic bone changes in the archaeological record may be other, extinct human-infecting-orthopoxviruses. Suggestions for further research: Further consideration of the implications of age of smallpox contraction on bony pathology: whether epiphyses are affected differently due to state of fusion. Reassessment of individuals previously identified with smallpox-consistent lesions, but otherwise diagnosed.
Keywords: Osteomyelitis variolosa; Variola virus; Non-adult; Viral infection; Elbow joint